2008
DOI: 10.1185/03007990802160834
|View full text |Cite
|
Sign up to set email alerts
|

Costs, quality of life, treatment satisfaction and compliance in patients with β-thalassemia major undergoing iron chelation therapy: the ITHACA study

Abstract: C o p y r i g h t I n f o r m a U K L i m i t e d 2 0 0 8 N o t f o r S a l e o r C o m e r c i a l D i s t r i b u t i o n U n a u t h o r i z e d u s e p r o h i b i t e d . A u t h o r i s e d u s e r s c a n d o w n l o a d ,Objectives: Iron chelation treatment (ICT) in -thalassemia major (-TM) patients undergoing blood transfusions can cause low satisfaction, low compliance, with possible negative consequences on treatment success, patients' wellbeing, and costs. The purpose was to estimate the societal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
2
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 29 publications
5
69
2
9
Order By: Relevance
“…The mean costs were € 1242/patient/month, 55.5% attributed to iron chelation therapy and 33.2% attributable to transfusions. 98 Moreover, proper medical therapy for TM requires advanced technologies such as cardiac or hepatic MRI. 30,99 With the combined cost of blood transfusions, chelation and management of complications, the requirements for optimal thalassemia care clearly exceed the health resources available in most non-industrialized countries.…”
Section: Cost and Cost Effectiveness For Tm And Scd Patientsmentioning
confidence: 99%
“…The mean costs were € 1242/patient/month, 55.5% attributed to iron chelation therapy and 33.2% attributable to transfusions. 98 Moreover, proper medical therapy for TM requires advanced technologies such as cardiac or hepatic MRI. 30,99 With the combined cost of blood transfusions, chelation and management of complications, the requirements for optimal thalassemia care clearly exceed the health resources available in most non-industrialized countries.…”
Section: Cost and Cost Effectiveness For Tm And Scd Patientsmentioning
confidence: 99%
“…This number has by and large remained static over the past decade. An Italian group reported in 2006, that the mean cost of treatment for thalassaemia major was € 1242/patient/month with 55.5% of it attributed to iron chelation therapy and 33.2% attributed to blood transfusion [2]. Bone marrow transplant (BMT) is the only established cure for thalassaemia at present.…”
Section: Correspondencementioning
confidence: 99%
“…This paper fails to portray the cardinal symptoms affecting the patients with MUO that the authors set out to palliate, the severity of such symptoms and the onset, duration and the degree of symptom improvement after RUS. Palliation should be viewed as a three-dimensional concept, namely onset, duration and degree of symptom relief [2]. Prophylaxis before surgery (9 cases), certainly not ureteric obstruction, should be excluded.…”
Section: Correspondencementioning
confidence: 99%
“…If patients are not feeling the beneficial effects of their therapy and particularly if they experience adverse events, they are not motivated to comply with the proposed treatment. One longitudinal multicenter, Italian-THAlassemia-Cost-and-outcomes-Assessment (ITHACA) 17 has previously reported a decrease in patient satisfaction and acceptance of their chelation therapy by deferoxamine, as the overall benefits were not always perceived as optimal. Another prospective, open-label, 1-year, multicenter study in the Middle East (ESCALATOR) 18 demonstrated that patients had greater satisfaction and convenience with Deferasirox compared to deferoxamine, which improved compliance and overall patient well-being.…”
Section: Effect On Renal Functionmentioning
confidence: 99%